The effect of sequential action of corrosion and fatigue on fatigue crack initiation and propagation in 2024-T3 aluminium alloy - Roungos, I. C. (Cranfield University, 1997)
The influence of sequential action of corrosion and fatigue on fatigue behaviour of 2024- T3 aluminium alloy was investigated. EXCO solution was used for corrosion development. Corrosion evolution and penetration were investigated in terms of exposure time, dimensional characteristics, orientation, microstructure of material, incremental corrosion application and sequential application of corrosion and fatigue. Single Edge Notch Tensile specimens were used in the fatigue-corrosion tests. Fatigue intervals were interrupted by corrosion application. Four fatigue intervals and four corrosion segment times were incorporated in the test matrix. The results of fatigue ínitiation, propagation and total life were compared to the virgin and pre-corroded materials' behaviour. The main mechanisms of crack acceleration and arrest were identified and discussed relative to the morphology of corrosion development. Finally a comparison was tried between the experimental lives and the predicted ones, calculated from two crack growth packages using the most conservative approach.